A Model for Creating Interactive eBooks for eLearning - Antonio Sarasa-Cabezuelo (Future Internet, 2020)
In recent decades, electronic books have revolutionized the publishing world. In this sense, an area of application is education, where electronic books can be used as educational resources to implement learning strategies about content and in eLearning environments. For this, it is necessary to introduce interactive elements in the electronic books that turn the reader into an active actor in the reading process. However, ebooks have a limitation regarding their creation process. In this sense, the tools can be user-oriented or programmer-oriented. The former are intuitive to use and have user-friendly interfaces, but they offer a reduced number of functionalities to add to books. The second are aimed at programmers, allowing for the implementation of any functionality, but limiting the number of content creators who can use them. The main motivation of this work is to propose an intermediate solution that offers a wide number of functionalities while not requiring deep programming knowledge to use them. In this sense, the solution of this article is novel since it proposes the use of extensible markup language (XML) documents to specify the structure of the electronic book in such a way that its processing will lead to the electronic book.